Search for supersymmetry in final states with missing transverse energy and 0, 1, 2, or at least 3 b-quark jets in 7 TeV pp collisions using the variable alphaT - CMS collaboration (2198 authors) (2013)
A search for supersymmetry in final states with jets and missing transverse energy is performed in pp collisions at a centre-of-mass energy of sqrt(s) = 7 TeV. The data sample corresponds to an integrated luminosity of 4.98 inverse femtobarns collected by the CMS experiment at the LHC. In this search, a dimensionless kinematic variable, alphaT, is used as the main discriminator between events with genuine and misreconstructed missing transverse energy. The search is performed in a signal region that is binned in the scalar sum of the transverse energy of jets and the number of jets identified as originating from a bottom quark. No excess of events over the standard model expectation is found. Exclusion limits are set in the parameter space of the constrained minimal supersymmetric extension of the standard model, and also in simplified models, with a special emphasis on compressed spectra and third-generation scenarios.